2016
DOI: 10.3329/seajph.v6i1.30343
|View full text |Cite
|
Sign up to set email alerts
|

Women empowerment through health seeking behavior in Bangladesh: Evidence from a national survey

Abstract: Empowering women is an important subject to achieve targets for the Sustainable Development Goals (SDGs) of Bangladesh. There are several indicators to measure the empowerment of women. Health seeking information is one of the most important indicators in this regard. This study aims at identifying the levels and patterns of women empowerment in relation to health seeking behavior in Bangladesh. Bangladesh Demographic and Health Survey (BDHS) 2011 data was used for the study. A total of 16635 women of reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
(9 reference statements)
2
17
0
Order By: Relevance
“…The lower the respondent's age, the more problems in accessing health care they faced. This finding was also stated in the study done in Bangladesh (6). In the study, access to health care of married women was better if they were married to educated and had white collar husbands.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The lower the respondent's age, the more problems in accessing health care they faced. This finding was also stated in the study done in Bangladesh (6). In the study, access to health care of married women was better if they were married to educated and had white collar husbands.…”
Section: Discussionsupporting
confidence: 74%
“…A group of study, mainly conducted in Asia and Africa, showed that women's empowerment is linked with contraception usage (6,7), lower fertility (8) and longer birth intervals (9). In Ghana, aspects of household decision-making, perceptions of spousal abuse, and spousal age differences were associated with women's utilization of health care.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The odds ratio analysis showed that married women who were currently working had higher odds of making their own decisions and this is consistent with research in Bangladesh. 35 Women from rural areas are more often decision makers than their urban counterparts but a different result was observed in Nepal where married women from urban areas were twice as likely to make their own decisions compared to rural women. 34 Married women who made their own decision were more likely to suffer from domestic violence and this is in line with another study in Pakistan where it has been found that women with decision making power are 2.29 times more likely to report experiencing violence by their husband/partner in their lifetime but Indian authors reported that women with decision making power are less likely to experience domestic violence.…”
Section: Discussionmentioning
confidence: 97%
“…In many areas-especially rural areas-men often control decisions about the health of their wives and children, including the family's use of health services [4,10]. A group of studies that were mainly conducted in Asia and Africa showed that women's empowerment is linked with contraception usage [11,12], lower fertility [13], and longer birth intervals [14].…”
Section: Introductionmentioning
confidence: 99%